2021
DOI: 10.1002/anie.202017070
|View full text |Cite
|
Sign up to set email alerts
|

Operando Investigation of Ag‐Decorated Cu2O Nanocube Catalysts with Enhanced CO2 Electroreduction toward Liquid Products

Abstract: Direct conversion of carbon dioxide into multicarbon liquid fuels by the CO 2 electrochemical reduction reaction (CO 2 RR) can contribute to the decarbonization of the global economy.H ere,w ell-defined Cu 2 On anocubes (NCs, 35 nm) uniformly covered with Ag nanoparticles (5 nm) were synthesized.W hen compared to bare Cu 2 ONCs,t he catalyst with 5at% Ag on Cu 2 ONCs displayed atwo-fold increase in the Faradaic efficiency for C 2+ liquid products (30 %a t À1.0 V RHE), including ethanol, 1-propanol, and acetald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
136
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(178 citation statements)
references
References 49 publications
14
136
0
1
Order By: Relevance
“…In practical electrochemical tests, the Cu 3 Ag 1 catalyst showed 63% FE for CO 2 to alcohol and an alcohol partial current density of 25 mA cm −2 at −0.95 V versus RHE, corresponding to a 126-fold enhancement in selectivity and 25-fold increase in activity compared with the bare electrodeposited Cu matrix. Herzog et al [91] investigated the morphology, chemical state, composition, and adsorbates of the well-defined Cu 2 O nanocubes (35 nm) uniformly covered with Ag NPs via ex situ, in situ, and operando characterization techniques under CO 2 RR conditions. Particularly, the redispersion was found for Ag NPs on Cu and a certain CuAg miscibility.…”
Section: Bimetal Strategymentioning
confidence: 99%
“…In practical electrochemical tests, the Cu 3 Ag 1 catalyst showed 63% FE for CO 2 to alcohol and an alcohol partial current density of 25 mA cm −2 at −0.95 V versus RHE, corresponding to a 126-fold enhancement in selectivity and 25-fold increase in activity compared with the bare electrodeposited Cu matrix. Herzog et al [91] investigated the morphology, chemical state, composition, and adsorbates of the well-defined Cu 2 O nanocubes (35 nm) uniformly covered with Ag NPs via ex situ, in situ, and operando characterization techniques under CO 2 RR conditions. Particularly, the redispersion was found for Ag NPs on Cu and a certain CuAg miscibility.…”
Section: Bimetal Strategymentioning
confidence: 99%
“…[22] Additionally, Ag incorporation in Cu weakens the binding energies of the reduced aldehyde intermediates and inhibits their further reduction to ethanol and 1-propanol as demonstrated in a recent DFT study. [23] However, the structural analysis of the catalysts showed that the surface partially consists of Cu/Ag areas, which also leads to the formation of ethanol and 1-propanol at the Cu sites, since they are expected to have higher binding energies for the oxygenated intermediates as compared to the Ag-Cu mixed regions. Therefore, having Ag/AgCu/Cu interfaces as active surface sites appear to enhance the yield of C2+ liquid products.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, a sequential-sites mechanism was adopted to illustrate the increased FEs of C 2 products on CuAu, CuAg, Cu x Zn, Ag/Cu 2 O catalysts. [47][48][49] Beyond that, the stability of Cu 2 O could be improved by introducing metal nanoparticles on Cu 2 O surface, such as our previously reported Cu 2 OÀ Au catalyst and nanoporous CuÀ Ag alloy catalyst. [12,23] In present work, we prepared the novel Au x Cu 2 O (x represents the molar mass of the introduction of Au) catalysts by the galvanic replacement reaction between cubic Cu 2 O and HAuCl 4 , and then the co-existence active sites of Cu + and Cu 0 on Au x Cu 2 O catalysts were generated by performing a repeated linear voltammetry (LSV) reduction before CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…When the second metal (Au, Zn, Ag) is introduced as an active promoter that forms more CO and could help generate a high flux of CO, so that neighboring Cu may have more opportunity to participate in C−C coupling. Therefore, a sequential‐sites mechanism was adopted to illustrate the increased FEs of C 2 products on CuAu, CuAg, Cu x Zn, Ag/Cu 2 O catalysts [47–49] . Beyond that, the stability of Cu 2 O could be improved by introducing metal nanoparticles on Cu 2 O surface, such as our previously reported Cu 2 O−Au catalyst and nanoporous Cu−Ag alloy catalyst [12,23] …”
Section: Introductionmentioning
confidence: 99%